Unraveling the Spatial Patterns of Everyday Life in Chinese Cities – A Comparative Study Between Beijing and Tianjin. Issue 9 (September 2014) - Sheng, Qiang
Abstract This paper presents a spatial research on the relationship between street pattern and the vitality of everyday life in the city center of Beijing and Tianjin. It illustrates how traditional street pattern as a hierarchical and introverted spatial structure is transformed by modern development and how this change can affect the use of local places. A detailed mapping of local shops inside 179 urban blocks in Beijing and 114 urban blocks in Tianjin was conducted. The space syntax software was utilized to measure the external and internal spatial conditions involved in the emergence and clustering of these shops. The findings suggest that even in the imported regular grid structure, local Chinese inhabitants still appropriate these extroverted spaces in an introverted way.